Corporate social responsibility and market exit decisions during geopolitical crises : Fortum’s exit from the Russian market - Ylitarvas, Aino (My University, 2025)
Corporate social responsibility (CSR) has gained a significant role in contemporary business. Governments, organizations and individuals demand that companies act responsibly and do not engage in irresponsible operations. At the same time, geopolitical crises have become more and more frequent. Economic tools are used to achieve geopolitical objectives in the powerplay between states. This makes the international business environment unpredictable and hard to navigate, which in turn exposes multinational enterprises (MNEs) to risks. Previous literature has found that companies are increasingly choosing normative responses in the face of geopolitical crises. This has brought to light the new generation of MNEs who take CSR seriously. The purpose of this thesis is to gain a deeper knowledge about how do MNEs uphold their CSR commitments when facing a serious geopolitical crisis in a host country. This is explored through a single case study by investigating the role of CSR as a driver of market exit decisions, identifying factors influencing market exit decisions beyond CSR and analyzing how do firms overcome market exit barriers. Different theories on CSR and market exits during geopolitical crises are used to form a theoretical framework for the study. One case company was chosen for the empirical part of this study. The study utilized both, secondary and primary data, with secondary data being main data source. Primary data was collected through expert interviews, whereas secondary data included the case company’s reports, website and independent news articles. These were carefully inspected and interpreted to gain a comprehensive understanding of the phenomenon. Upholding CSR commitments in the face of serious geopolitical crises in not straightforward. Arriving at a certain exit decision and carrying it out is influenced by many factors, including reputational damage and operational costs for example. The findings of this study suggest that CSR strategies play a fundamental role in formulating responses to geopolitical crises. External pressures and internal values were found to preserve normative resilience when exit barriers are interfering with the process. To manage exit barriers, companies might need to renew their strategy, which can lead to greater emphasis of CSR related issues.

Yritysvastuulla on merkittävä rooli nykypäivän liiketoiminnassa. Valtiot, organisaatiot ja yksilöt edellyttävät yrityksiltä johdonmukaista vastuullista toimintaa. Samaan aikaan geopoliittiset kriisit ovat yleistyneet. Taloudellisia keinoja käytetään yhä useammin geopoliittisten päämäärien saavuttamiseen valtioiden välisessä valtapelissä. Tämä tekee kansainvälisestä liiketoimintaympäristöstä ennakoimattoman ja vaikeasti hallittavan, mikä puolestaan altistaa monikansallisia yrityksiä riskeille. Aiempi tutkimus on osoittanut, että nykyään yritykset toimivat usein arvojensa pohjalta kohdatessaan geopoliittisia kriisejä. Ilmiö on nostanut esiin uuden sukupolven monikansallisia yrityksiä, jotka suhtautuvat yritysvastuuseen vakavasti. Tämän tutkielman tarkoituksena on syventää ymmärrystä siitä, miten monikansalliset yritykset pystyvät pitämään kiinni yritysvastuuteen liittyvistä sitoumuksistaan vakavien geopoliittisen kriisien puhjetessa. Aihetta tarkastellaan tapaustutkimuksen keinoin. Tutkielmassa tutkitaan yritysvastuun roolia markkinoilta vetäytymisen taustalla, tunnistetaan muita vetäytymispäätöksiin vaikuttavia tekijöitä sekä analysoidaan, miten yritykset käsittelevät markkinoilta poistumisen esteitä. Tutkielmassa hyödynnetään laajasti erilaisia yritysvastuuta ja markkinoilta vetäytymistä käsitteleviä teorioita teoreettisen viitekehyksen rakentamiseksi. Empiiristä osaa varten valittiin yksi tapausyritys. Tutkimuksessa hyödynnettiin sekä toissijaista että ensisijaista aineistoa, joista toissijainen oli pääasiallinen lähde. Ensisijainen aineisto kerättiin asiantuntijahaastattelujen avulla. Toissijainen aineisto taas koostui tapausyrityksen raporteista, verkkosivuista ja riippumattomista uutisartikkeleista. Näitä aineistoja tarkasteltiin ja tulkittiin huolellisesti, jotta ilmiöstä saataisiin mahdollisimman kattava ymmärrys. Yritysvastuuseen liittyvien sitoumusten noudattaminen vakavien geopoliittisten kriisien aikana ei ole yksiselitteistä. Vetäytymispäätöksiin vaikuttavat monet tekijät, kuten esimerkiksi mainehaitta ja taloudelliset kustannukset. Tutkimuksen tulokset viittaavat kuitenkin siihen, että yritysvastuustrategiat ovat keskeisessä asemassa geopoliittisiin kriiseihin reagoitaessa. Erityisesti ulkoinen paine toimia oikein ja yrityksen sisäiset arvot näyttäytyvät normatiivisen resilienssin ylläpitäjinä silloin, kun markkinoilta poistumisen esteet hankaloittavat prosessia. Vetäytymisen esteiden hallitsemiseksi yritysten voi olla tarpeen uudistaa strategiaansa, mikä voi osaltaan johtaa yritysvastuun strategiseen korostumiseen.
Keywords: corporate social responsibility, market exit, geopolitical crises, geopolitical risks, normative resilience, Russia, case study